Introduction of the euro and the monetary policy of the European Central Bank - Hamori, Shigeyuki 1959- (World Scientific Pub. Co., 2010)
The Euro area is an extremely unique and important currency area for two reasons. First, it is the single largest currency area to be created in an industrialized region and is important as a test case for regions contemplating the establishment of new currency areas, such as East Asia and North America. Second, it was established by sovereign states working as peers, which, despite various challenges, peacefully and autonomously decided to create a single currency area. Marking the 10th anniversary of the creation of the European Central Bank (ECB) and the Euro, this invaluable book analyzes the monetary policy of the ECB - the guardian of the Euro - by using recently developed econometric methods. The analysis performed in this book marks a substantial contribution toward understanding the significance of the Euro area as well as the future of the Euro from an international perspective